2002
DOI: 10.1002/cne.10253
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and distribution of a novel neuropeptide, Rana RFamide (R‐RFa), in the brain of the European green frog Rana esculenta

Abstract: A novel neuropeptide of the RFamide peptide family was isolated in pure form from a frog (Rana esculenta) brain extract by using reversed-phase high performance liquid chromatography in combination with a radioimmunoassay for mammalian neuropeptide FF (NPFF). The primary structure of the peptide was established as Ser-Leu-Lys- Pro-Ala-Ala-Asn-Leu-Pro-Leu- Arg-Phe-NH(2). The sequence of this neuropeptide, designated Rana RFamide (R-RFa), exhibits substantial similarities with those of avian LPLRFamide, gonadotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 150 publications
4
70
0
2
Order By: Relevance
“…1A. Absorbance was measured at 215 and 280 nm, and eluting fractions were assayed for NPFF-like immunoreactivity (NPFF-LI) as described (2). Fraction 61 was selected for further purification and successively chromatographed on a 0.46 ϫ 25-cm Shodex C8P-50 4E C 8 column, a 0.46 ϫ 25-cm Vydac 218TP54 C 18 column, a 0.46 ϫ 25-cm Shodex C8P-50 4E C 8 column, and a 0.46 ϫ 25-cm Vydac 218TP54 C 18 column, at a flow rate of 1 ml͞min, by using the elution conditions indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A. Absorbance was measured at 215 and 280 nm, and eluting fractions were assayed for NPFF-like immunoreactivity (NPFF-LI) as described (2). Fraction 61 was selected for further purification and successively chromatographed on a 0.46 ϫ 25-cm Shodex C8P-50 4E C 8 column, a 0.46 ϫ 25-cm Vydac 218TP54 C 18 column, a 0.46 ϫ 25-cm Shodex C8P-50 4E C 8 column, and a 0.46 ϫ 25-cm Vydac 218TP54 C 18 column, at a flow rate of 1 ml͞min, by using the elution conditions indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, several FMRFamide-related peptides (RFRPs), which all possess the Arg-Phe-NH 2 motif at their C terminus, have been isolated in various groups of invertebrates (see ref. 2 for review), and it has been found that a single species may express multiple members of RFRPs. In particular, in Caenorhabditis elegans, 22 genes encoding 59 distinct RFRPs have been identified (3).…”
mentioning
confidence: 99%
“…The isolated LPLRF-amide peptide from bullfrog hypothalami possessed growth hormone-releasing activity, and was designated as frog growth hormone-releasing peptide (fGRP) (Koda et al 2002). This fGRP is structurally identical to Rana RF-amide (R-RFa) purified by Chartrel et al (2002). The fGRP precursor also encoded one fGRP and three related peptides (fGRP-RP-1, -2, and -3; Sawada et al 2002a), which were identified as mature LPXRF-amide peptides (Ukena et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…neuropeptide FF (NPFF), neuropeptide AF (NPAF) and neuropeptide SF (NPSF) [4][5][6][7][8]; (b) LPXRFamide (X = L or Q) peptide group, e.g. gonadotropin-inhibitory hormone (GnIH), mammalian RFamide-related peptides (RFRPs), frog growth hormone-releasing peptide (fGRP) and goldfish LPXRFamide peptide (gfLPXRFa) [9][10][11][12][13][14][15][16][17][18][19][20]; (c) prolactin-releasing peptide (PrRP) group, e.g. PrRP31, PrRP20, crucian carp RFamide (C-RFa), salmon RFa and tilapia PrRP [21][22][23][24]; (d) metastin group, e.g.…”
Section: Introductionmentioning
confidence: 99%